Optimization of costs in the enterprise. Effective strategies for business - N. Yu. Pracheva (Путеводитель предпринимателя)
The article is devoted to an effective methods of cost optimization in small business. All of them, used at the right time, make it possible to improve the situation and maximize profits by reducing costs.«The process of cost optimization cannot be started for a while and then stopped. It is necessary to understand that business process, investment and procurement management should be considered in the long term from the point of view of cost optimization. First of all, it concerns new projects, new equipment and new technologies» — the most important thesis of this article. The author offers an algorithm of actions for entrepreneurs who are ready to solve the optimization problem in a complex way.